On tests for long memory process behavior of international tourism market: Thailand and India - Sriboonchitta, Songsak; Chaitip, Prasert; Balogh , Péter; Kovács , Sándor; Chaiboonsri , Chukiat (Applied Studies in Agribusiness and Commerce, 2011)
In our research we examine the behaviour of both Thailand’s and India’s international tourism market by using long-memory analysis. The international tourism market of Thailand combined with seven groups such as East Asia, Europe, The Americas, South Asia, Oceania, Middle East and Africa. Similarly, the international tourism market of India combined with nine countries: USA, UK, Canada, Germany, France, Japan, Malaysia, Australia and Sri Lanka. Moreover, three statistical tests for long-memory process such as R/S test, Modified R/S test and GPH-test are employed to study these markets. The empirical findings in general provide more support for long memory process in international tourism market of Thailand and evidence for short-term dependence in international tourism market of India. Therefore, the policy makers of each country should understand the behaviour of long memory process in international tourism market before launching any stimulating campaign to this industry.